2015
DOI: 10.2308/accr-51049
|View full text |Cite
|
Sign up to set email alerts
|

Why do Restatements Decrease in a Clawback Environment? An Investigation into Financial Reporting Executives' Decision-Making during the Restatement Process

Abstract: Prior archival studies find that firms that voluntarily adopted clawback policies have experienced a reduction in restatements. I experimentally examine this outcome by investigating the influence of two key factors (i.e., executive compensation structure and auditor quality) on financial reporting executives' (hereafter, “executives”) decision-making regarding a proposed restatement that will lead to a clawback of their incentives. I find that executives (i.e., CFOs, controllers, and treasurers) facing a lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Specifically, deHaan, Hodge, and Shevlin (2013) find that restatements decreased for companies that voluntarily adopted a clawback policy compared to companies that did not adopt such a policy. Yet, prior to Pyzoha (2015), no study had previously examined executive behavior during the restatement process when their incentive compensation was at risk of being clawed back.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, deHaan, Hodge, and Shevlin (2013) find that restatements decreased for companies that voluntarily adopted a clawback policy compared to companies that did not adopt such a policy. Yet, prior to Pyzoha (2015), no study had previously examined executive behavior during the restatement process when their incentive compensation was at risk of being clawed back.…”
Section: Motivationmentioning
confidence: 99%
“…T his article summarizes a recently published study titled ''Why do Restatements Decrease in a Clawback Environment? An Investigation into Financial Reporting Executives' Decision-Making during the Restatement Process'' (Pyzoha 2015). We discuss the study's motivation, hypotheses, research method, and results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOX provisions were reinforced by the Dodd-Frank Act, 2010. Surprisingly, Pyzoha (2015) presented empirical evidence that suggests that clawbacks may have the opposite effect to that intended. By effectively imposing a financial penalty on executives for financial restatement, the likelihood of financial restatements is inhibited.…”
Section: Sox and Its Implications For Ethical Behavior In Organizationsmentioning
confidence: 99%
“…No other published study has reported that a benefit of clawback provisions is mitigating ex post overinvestment. Prior studies investigated the impact of firms' voluntary adoption of clawback provisions on their financial reporting quality and the market's reaction to these voluntary adoptions (e.g., Brown, Davis-Friday, Guler, & Marquardt, 2015;Cashman, Harrison, & Panasian, 2016;Chan et al, 2012;Dehaan et al, 2013;Iskandar-Datta & Jia, 2013;Pyzoha, 2015). However, little is known about whether clawback provisions affect executives' investment behavior.…”
Section: Introductionmentioning
confidence: 99%